OUTCOMES OF SURGICAL TREATMENT OF POSTERIOR CRUCIATE LIGAMENT TIBIAL AVULSION FRACTURES USING SCREW FIXATION AT MILITARY CENTRAL HOSPITAL 108 - Mai Duc Thuan; Le Quang Vu (Tạp chí Y học Quân sự, 2026)
Objective: To evaluate the results of open surgery (reduction and fixation with cannulated cancellous screws) in the treatment of posterior cruciate ligament tibial avulsion fractures at Military Central Hospital 108. Subjects and methods: A retrospective descriptive study was conducted on 29 patients with posterior cruciate ligament tibial avulsion fractures who had indications for and underwent open reduction and fixation of the posterior cruciate ligament tibial avulsion fracture using cannulated cancellous screws at Military Central Hospital 108 from January 2022 to December 2025. Treatment outcomes were evaluated according to the Lysholm score, IKDC classification, range of motion, postoperative knee laxity, bone union status, ability to return to pre-injury activities, and postoperative complications. Results: The mean age of the study patients was 31.31 ± 8.39 years, with males accounting for 82.8%; most injuries were caused by traffic accidents (72.4%). The mean postoperative follow-up period was 13.51 ± 1.52 months. The Lysholm score improved significantly (from 28.10 ± 2.45 to 89.52 ± 3.11 points, with a mean increase of 61.41 ± 4.28 points, p < 0.001). The proportion of patients with good and excellent postoperative Lysholm scores was 93.1%; IKDC classification grades A and B accounted for 93.1%; knee range of motion ≥ 120° was achieved in 93.1%; and 82.8% had no residual knee laxity. Within 6 months after surgery, 100% of patients achieved bone union; 86.2% returned to their pre-injury activity level; and 1 patient was noted to have mild joint effusion. Conclusion: Open reduction and fixation with cannulated cancellous screws for the treatment of posterior cruciate ligament tibial avulsion fractures is safe and yields favorable outcomes, helping to restore good function, provide stable fixation, achieve a high bone union rate, and maintain a low complication rate.